New opportunities in laboratory diagnostics of shot products by their x-ray fluorescence spectral element analysis. - Mishalov, V. D.; Michailenko, O. V. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Optical Spectroscopic techniques widely used in practice despite the high sensitivity and wide range of studied chemical elements have the drawbacks, such as sample preparation, which is possible only in case of destruction of the investigated object. Non-destructive method to investigate the elemental composition of metal layers and other products of the shot is X-ray fluorescence spectral analysis, but the knowledge about the possibilities of modern equipment is incomplete. Objective. Identify chemical elements in damage simulator clothes at experimental shots from firearms through X-ray fluorescence spectral element analysis using a spectrometer «M4 TORNADO» manufactured by Bruker. Methods. The object of study was damaged clothe (patches of leather of jacket). Micro X-ray fluorescence spectral element analysis with a spectrometer «M4 TORNADO» manufactured by Bruker (Germany) was applied. Results. Use of technical capabilities and software spectrometer «M4 TORNADO» provides new opportunities for laboratory diagnosis of various chemical elements in the tissues of biological and non-biological origin, including shot products through micro X-ray fluorescence spectral element analysis. Its advantages over similar methods are the possibility of mapping the topography as common maps of elements, maps for individual elements and their combinations. Analyzing the distribution pattern of elements on maps researcher has an opportunity to interpret the character of layers and background concentrations of the elements by their intensity. Conclusion. Tested equipment and program software opens new opportunities for laboratory diagnostics of shot products by their X-ray fluorescence spectral element analysis.